Asuhan Keperawatan pada Ny.N dengan Diabetes Melitus Tipe II di Ruang Interne RSUD Prof. M. Yamin, SH Pariaman Tahun 2026 - Sri Wulandari; Linda Marni; Debby Silvia Dewi; Hilma Yessi (PPNI UNIMMAN, 2026)
Diabetes Mellitus Type II is a chronic metabolic disease characterized by elevated blood glucose levels due to insulin resistance and impaired insulin secretion. Globally, the number of people with diabetes in 2024 is estimated to reach 800 million, with more than 95% being Type II Diabetes Mellitus. At RSUD Prof. M. Yamin, SH Pariaman in 2025, there were 189 recorded cases of Type II Diabetes Mellitus without complications. The purpose of this scientific paper is to provide nursing care to a patient with Type II Diabetes Mellitus in the Internal Medicine Ward of RSUD Prof. M. Yamin, SH Pariaman. The method used is a case study with a nursing process approach, including observation, interviews, physical examination, and data collection from medical records. This study was conducted in the internal ward for 5 days, from February 6, 2026 to February 10, 2026, with the subject Mrs. N. The assessment results identified nine nursing problems: unstable blood glucose levels, acute pain, impaired skin/tissue integrity, ineffective peripheral perfusion, impaired physical mobility, sleep pattern disturbance, fatigue, risk of infection, and risk of nutritional deficit. The evaluation after 5 days of nursing care showed that five diagnoses were resolved, namely unstable blood glucose levels, ineffective peripheral perfusion, fatigue, risk of infection, and risk of nutritional deficit. Meanwhile, the other four diagnoses were not fully resolved but showed improvement. It is expected that the patient and family will maintain adherence to a healthy lifestyle, therapy, diet, and regular follow-up in order to prevent complications.